Robust Three-Loop Trajectory Tracking Control for Quadrotors With Multiple Uncertainties - Liu, Hao; Li, Danjun; Zuo, Zongyu; Zhong, Yisheng (IEEE transactions on industrial electronics (1982), 2016)
In this paper, a robust decentralized and linear time-invariant controller is proposed for quadrotors to achieve trajectory tracking. The designed closed-loop control system includes three loops: (1) an attitude loop that controls the attitude angles; (2) a position loop that controls the translational trajectory of the quadrotor; and (3) a robust compensating loop that restrains the influence of uncertainties including parameter uncertainties, nonlinear and coupling dynamics, and external disturbances in the rotational and translational dynamics. It is proven that the tracking errors can converge into a priori set neighborhood of the origin ultimately. Experimental results are given to confirm the advantages of the proposed control method, compared with the linear time-invariant H ∞ control method.